Students friendly medical examination - Chaurasia, Rakesh Chandra (International Journal of Basic & Clinical Pharmacology, 2017)
Undergraduate medical education is very vast area comprises of over dozen subjects and their evaluation through professional examination. In current scenario of modern life students are pressurized from every corners, economic burden, lack of proper teaching or friendly environment, senior and peer group pressure, love affairs are common issues during college life. Insecurity of job after completion of education will pose future financial fear. These are some common reasons enough to pressurized, therefore incidence of depression and suicidal tendencies are going on to be increases several folds among medicos. In current scenario of tough life, medical examination is always a burden. The professional exams of universities are the matter of their norms and regulation, but we have day-to-day assessment through-out duration; this is enough to moralize them and prepare before final professional examination.